Hacia la Reforma Agraria Popular en Paraguay - Setrini, Gustavo (2023)
One of the main political events of the 20th century for Latin America was the agrarian reform. The policies implemented in its name and the various understandings of the agrarian issue unfolded from different actors' proposals for solutions. Agrarian reforms were defined as land distribution policies carried out primarily through expropriation or with market assistance. The economic and political transformations of recent decades have led social actors grouped in the peasant movement to reconsider the definition of agrarian reform. What is the agrarian reform currently needed, how does it differ from previous ones, and what productive and trade policies will be necessary for its effective implementation? After identifying "Popular Agrarian Reform" as the response of the peasant movement to current agrarian issues, this article concludes that planning policies for the agrifood system, especially its productive and commercial links, are essential for the realization of popular agrarian reform.